The influence of a reality radio program on HIV/AIDS in Malawi: Results from a pilot study. (1st October 2016) - Limaye, Rupali J.; Brown, Jane; Berman, Amanda; Roberts, Peter; Kakhobwe, Triza
Abstract: Introduction : HIV/AIDS is the leading cause of death in Malawi. Stigma surrounding voluntary counseling and testing and multiple sexual partnerships are key factors. Mass media programing, including radio, can reduce HIV risk of exposure by motivating people to take protective behavioral action. However, little is known about how health communication in the form of reality radio can influence HIV/AIDS-related behaviors. Objectives : This study sought to understand the impact of a reality radio program on HIV/AIDS testing and multiple sexual partnerships among Malawians. Methods : This study analyzed radio listener feedback in the form of text messages. Results : Listeners reported that the reality radio program helped them understand the importance of HIV testing, enhanced their HIV/AIDS risk perception, aided them in becoming faithful within marriages, and enhanced their understanding of the consequences of multiple sexual partnerships on their families. Conclusions : Reality radio approaches have not been studied widely, and, based on the results of this study, should be further explored as an innovative health communication approach for health behavior change.